Effects of daylight on motivation and satisfaction levels of government employees at the Philippine House of Representatives - Dizer, Raiya Edith R.
Literature points to the relationship between job motivation, level of satisfaction, and light in the work environment. This study investigated this relationship of daylight, job satisfaction and motivation of government employees at the House of Representatives by taking access to daylight into account. The lower ground floor offices in the North & South Wings of the House of Representatives have workspaces of varied light exposure which the following conditions: no windows, with windows but blocked, and with windows and daylight access. In order to establish the correlation between daylighting and the motivation of the employees, the study used a cross-sectional and non-experimental study design. A random sample of thirty respondents from a population of approximately 170 employees who hold administrative, managerial, and clerical positions were asked to respond to a one-page questionnaire. Observations of actual operations on a typical working day were also conducted to supplement the result of the survey. The observations resulted in the identification of three types of office environments. The survey data were analyzed using the Likert scale method. Findings from this study pointed to the positive relationship between lighting, motivation, and level of satisfaction. Light as well as the physical environment of the office was found to affect the mood of employees. Daylight made employees feel good at work and, with its presence the employees also reported their expectation that there would be an improvement in their task performance. Likewise, there was general agreement from employees belonging to the work-environment groups that absence of daylight caused stress. Overall, there's a general perception among the respondents that the presence of daylight is related to the motivation to work.